A Dy4 Cubane: A New Member in the Single‐Molecule Toroics Family. (27th November 2018) - Fernandez Garcia, Guglielmo; Guettas, Djamila; Montigaud, Vincent; Larini, Paolo; Sessoli, Roberta; Totti, Federico; Cador, Olivier; Pilet, Guillaume; Le Guennic, Boris
Abstract: Molecular materials that possess a toroidal moment associated to a non‐magnetic ground state are known as single‐molecule toroics (SMTs) and are usually planar molecules. Herein, we report a Dy4 cubane, namely [Dy4 (Bppd)4 (μ3 ‐OH)4 (Pa)4 (H2 O)4 ]⋅0.333 H2 O (where BppdH=1, 3‐Bis(pyridin‐4‐yl)propane‐1, 3‐dione and PaH=2‐Picolinic acid) for which magnetometry measurements and state‐of‐art ab initio calculations highlight SMT behavior in a tridimensional structure (3D‐SMT). The in‐depth theoretical analysis on the resulting low‐lying energy states, along with their variation in function of the magnetic exchange pathways, allows further light to be shed on the description of single‐molecule toroics and identify the coupling scheme that better reproduces the observed data. Abstract : Besondere Momente : Molekulare Materialien mit einem toroidalen Moment, das einem nichtmagnetischen Grundzustand zugehörig ist, werden als Einzelmolekültoroika (SMTs) bezeichnet und sind üblicherweise planare Moleküle. Ein solches toroidales Moment wurde nun für ein Dy4 ‐Cuban beobachtet, was diese Eigenschaft auf dreidimensionale Strukturen ausdehnt (3D‐SMTs).